2015
DOI: 10.1515/ijamh-2013-0341
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of adolescents with eating disorders from an adolescent medicine service at a large children’s hospital

Abstract: Earlier detection and referral of adolescents with eating disorders are needed because a high percentage of patients, especially those with anorexia nervosa, required hospitalization at initial contact. The benefits of inpatient admission may extend beyond medical stabilization of the most medically compromised patients to include improved therapeutic relationship with the treatment team and improved follow-up. Many patients prematurely terminate treatment; factors contributing to premature termination of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…length and number of in-patient, day-patient and/or out-patient episodes). This resonates with findings by Hergenroeder et al 27 indicating that repeated admissions for eating disorder treatment during adolescence are associated with poor recovery. These findings highlight clinical identification in CAEDS of the likelihood for ongoing treatment into young adulthood and supports the notion that quick resolution of eating disorders in childhood/adolescence is optimal.…”
Section: Discussionsupporting
confidence: 90%
“…length and number of in-patient, day-patient and/or out-patient episodes). This resonates with findings by Hergenroeder et al 27 indicating that repeated admissions for eating disorder treatment during adolescence are associated with poor recovery. These findings highlight clinical identification in CAEDS of the likelihood for ongoing treatment into young adulthood and supports the notion that quick resolution of eating disorders in childhood/adolescence is optimal.…”
Section: Discussionsupporting
confidence: 90%
“…The Pubmed search resulted in 192 titles for inspection and 7 abstracts for inspection of which 5 were not trials of treatment setting [28][29][30][31][32] and one was a review [33] and one new trial [34] was identified. The CCRCT Issue 6 of 12, June 2014 (n = 797723) search resulted in 20 titles for inspection of which two were duplicates and one new trial [29] was identified ( Figure 1).…”
Section: Results Of Searchmentioning
confidence: 99%
“…While many patients can be managed in the outpatient setting, some require inpatient admission for medical stabilization. One study by Hergenroeder, Wiemann, Henges, and Dave () found that being hospitalized once and longer duration of follow‐up was associated with partial or full recovery in patients with eating disorders. Hospitals may benefit from having the essential disciplines available to care for admitted patients with AN and malnutrition.…”
Section: Discussionmentioning
confidence: 99%